RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN MENGGUNAKAN METODE FUZZY TSUKAMOTO - Sumarsono Patti, Tito; Hilmy, Zakwan (JURNAL JALASENA, 2024)
Appreciation of employee performance is very necessary in a company to improve the quality of performance and work enthusiasm for employees. One of them is SUBCON MICRO ENGINEER which operates in the field of distribution and installation of ducting installations. This company gives appreciation in the form of bonuses to its employees. The existing bonus calculation uses several criteria such as the employee's length of service and the employee's net salary. From the criteria obtained, it can be calculated using the Fuzzy Tsukamoto method, then creating decisions in the form of few and many variables. Once the variable decision is obtained, it will produce a nominal employee bonus.